2018
DOI: 10.26493/1854-6935.16.59-77
|View full text |Cite
|
Sign up to set email alerts
|

Education and Economic Growth: Empirical Evidence from Nigeria

Abstract: Experts opined that education affects the society both at the micro and macro levels. However, the place of education has not been given its right place in Nigeria as reflected in the nation's budgetary allocations. Hence, this study examined the impact of different levels of education on different components of growth in Nigeria. Data were sourced from the cbn Statistical Bulletin (see http://www.cbn.gov.ng/documents/statbulletin.asp), the Nigerian Bureau of Statistics (see http://www.nigerianstat.gov.ng) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Different levels of education contribute differently to the economy, and higher education is considered as an important factor in enhancing economic competitiveness [9]. Other studies have concluded that secondary education contributes far more to the economy than primary and university education [10]. In China's system, compulsory education and cognitive skills do not significantly directly or indirectly contribute to economic growth.…”
Section: The Contribution Of Education Improvement To Rapid Economic ...mentioning
confidence: 99%
“…Different levels of education contribute differently to the economy, and higher education is considered as an important factor in enhancing economic competitiveness [9]. Other studies have concluded that secondary education contributes far more to the economy than primary and university education [10]. In China's system, compulsory education and cognitive skills do not significantly directly or indirectly contribute to economic growth.…”
Section: The Contribution Of Education Improvement To Rapid Economic ...mentioning
confidence: 99%
“…Framework. Ample literature loudly voiced the importance of human capital as it plays a pivotal role in the holistic development of the nation [10][11][12][13][14][15][16][17]. As a theory, HC has got broader acceptance with the contribution of scholars like Sheltuz, Mencer, and Beker, who shifted the thinking philosophy of policymakers by emphasizing the centrality of HC in the development process in the 1960s [1,2,18].…”
Section: Conceptual and Eoreticalmentioning
confidence: 99%
“…is was, in fact, with the inherent capacity of human beings to acquire new knowledge, skills, and attitudes and his ability to adapt to new technologies and take part in creating innovative ways of doing things. In this regard, education plays a pivotal role in realizing this potential [11,15]. is actually remains the base for HC discourses among researchers and policymakers [7,20].…”
Section: Conceptual and Eoreticalmentioning
confidence: 99%
“…In other words, the level of education of someone can increase productivity, whether in their own individual capabilities as well as easiness in adapting to technology. Eregha et al (2015) conducted a research in Nigeria during 1970-2015 using the approach of analysis of Error Correction (OLS), Fully Modified OLS (FMOLS), and Dynamic OLS (DOLS). The research result shows that the level of education and completion rate gives a positive influence toward economic growth in Nigeria.…”
Section: Educationmentioning
confidence: 99%